2022
DOI: 10.3389/fnut.2022.878791
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Preoperative Sarcopenia in Patients With Gastric Cancer Liver Metastases Receiving Hepatectomy

Abstract: BackgroundThe present work focused on assessing the role of computed tomography (CT)-determined sarcopenia in the prognosis of patients with gastric cancer liver metastases (GCLM) receiving hepatectomy.MethodsWe analyzed data collected from GCLM cases that underwent hepatectomy between March 2011 and July 2017. The third lumbar vertebra (L3) level skeletal muscle index (SMI) was analyzed by abdominal CT to determine the sarcopenia before surgery. The thresholds for CT-based sarcopenia of sex-specific L3 SMI we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Additionally, it shows significant relation with the poor long-term prognosis among patients with GC receiving surgery (14). Our previous work indicated that sarcopenia effectively predicted prognosis of recurrence in patients with GCLM receiving hepatectomy (15). The Peking prognostic score (PPS), first proposed by Xiong et al, consists of sarcopenia and LCR and shows high relation to GC prognosis (16).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it shows significant relation with the poor long-term prognosis among patients with GC receiving surgery (14). Our previous work indicated that sarcopenia effectively predicted prognosis of recurrence in patients with GCLM receiving hepatectomy (15). The Peking prognostic score (PPS), first proposed by Xiong et al, consists of sarcopenia and LCR and shows high relation to GC prognosis (16).…”
Section: Introductionmentioning
confidence: 99%